EKONOMI RUMAH TANGGA, DISTRIBUSI PENDAPATAN DAN KEMISKINAN DI DUA DESA DI JAWA TENGAH DAN DIY: Studi Kasus di Batus (Klaten) dan Semanu (Gunung Kidul) - Tadjuddin Noer Effendi; Wini Tamtiari; Susi Eja Yuarsi; Sukamtiningsih Sukamtiningsih (Populasi, 1993)
This study examines the household economy, income distribution, extent of poverty, and factors that determine the poverty level of two villages in Central Java and Yogyakarta. By using data from household and industry surveys, this study found that lack of employment opportunities in the agriculturalsector hasforced many rural workers looking for non-farm employment, both in rural and urban areas. Rural non-farm activities, especially rural industries, have a positive impact in reducing poverty both in less developed and indeveloped villages. As can be expected this study also found that poverty is more common in less developed than developed areas. However, inequality in income distribution is more pronounced in developed villages. This means that poverty and income distribution are quite different problems. Accordingly, solutions to these problems have to be different.